Technogenic impact of fuels and lubricants on the natural environment during the operation of helicopters - Yefymenko, Valerii; Kalmykova , Nataliia (Problems of Environmental Biotechnology, 2021)
Peculiarities of pollution of airports and flight paths with exhaust gases of modern aircraft engines are considered.